Stipa barbata Desf. (Poaceae, Sect. Barbatae Junge) una nueva especie para la flora de la provincia de Valencia. - Ferrer-Gallego, Pedro Pablo (Acta Botanica Malacitana, 2007)
Stipa barbata Desf. (Sect. Barbatae Junge) a new species for the Valencia province flora Palabras clave. Stipa barbata, Poaceae, Sect. Barbatae, corología, Valencia, Península Ibérica Key words. Stipa barbata, Poaceae, Sect. Barbatae, chorology, Valencian province, Iberian Peninsula